AGIG Chemo-Immunotherapy in Patients With Advanced Pancreatic Cancer: A Single-Arm, Single-Center, Phase 2 Study - Dai, Wangshu; Qiu, Xin; Lu, Changchang; Zou, Zhengyun; Sha, Huizi; Kong, Weiwei; Liu, Baorui; Du, Juan (Frontiers in Oncology, 2021)
Background: To date, chemotherapy remains the only effective treatment of unresectable pancreatic adenocarcinoma. In the past few years, the interest in immunological anticancer therapy rises sharply. AGIG is a novel chemo-immunotherapy regimen that combines nab-paclitaxel + gemcitabine chemotherapy with sequential recombinant interleukin-2 (IL-2) and granulocyte-macrophage colony stimulating factor (GM-CSF) therapy. We conducted a single-arm prospective phase II study to determine the efficacy and safety of the first-line treatment of advanced pancreatic cancer with AGIG regimen. Methods: Nab-paclitaxel (125 mg/m2) and gemcitabine (1000 mg/m2) were administered intravenously to all patients on days 1 and 8 triweekly, interleukin-2 (1000000U) and GM-CSF (100 µg) were administered subcutaneously on days 3-5 after chemotherapy. The primary end point was ORR by the Response Evaluation Criteria in Solid Tumors, version 1.1. Secondary end points included safety profile, progression-free survival (PFS), overall survival (OS). Patients’ conditions along wtih the efficacy and safety were assessed every two cycles. Results: Between 11/2018 and 01/2020, sixty-four patients were enrolled. In the sixty-four evaluable patients, the disease control rate (DCR) and overall response rate (ORR) were 76.6% and 43.75%, respectively. The median follow-up time was 12.1 (range 7.1–22.4) months. The median PFS was 5.7 (range 1.63–15.8) months. The median OS was 14.2 (range 2.9–22.0) months. The most common adverse event was fever (75%). The incidence of III/ IV grade neutropenia was 4.69%. In subgroup analyses, we found that eosinophil count in the blood elevated three times higher than baseline level predicted a longer survival. Conclusions: The AGIG chemo-immunotherapy regimen has presented favorable ORR, OS, and manageable toxicities as first-line therapeutic strategy of advanced pancreatic cancer treatment. This regimen may be a novel reliable therapeutic option for patients with preserved performance status. The improvement of treatment efficiency may be related to the activation of non-specific immune response.